Differential Microbial Signature Associated With Benign Prostatic Hyperplasia and Prostate Cancer - Sarkar, Purandar; Malik, Samaresh; Banerjee, Anwesha; Datta, Chhanda; Pal, Dilip Kumar; Ghosh, Amlan; Saha, Abhik (Frontiers in Cellular and Infection Microbiology, 2022)
Apart from other risk factors, chronic inflammation is also associated with the onset of Prostate Cancer (PCa), wherein pathogen infection and tissue microbiome dysbiosis are known to play a major role for both inflammatory response and cancer development. However, except for a few studies, the link between microbes and PCa remained poorly understood. To explore the potential microbiome signature associated with PCa in Indian patients, we investigated differential compositions of commensal bacteria among patients with benign prostatic hyperplasia (BPH) and PCa using 16S rRNA amplicon sequencing followed by qPCR analyses using two distinct primer sets. Using two independent cohorts, we show that Prevotella copri, Cupriavidus campinensis and Propionibacterium acnes represent three most abundant bacteria in diseased prostate lesions. LEfSe analyses identified that while Cupriavidus taiwanensis and Methylobacterium organophilum are distinctly elevated in PCa samples, Kocuria palustris and Cellvibrio mixtus are significantly enriched in BPH samples. Furthermore, we identify that a number of human tumor viruses including Epstein-Barr virus (EBV), hepatitis B virus (HBV) along with two high risk human papillomaviruses - HPV-16 and HPV-18 are significantly associated with the PCa development and strongly correlated with PCa bacterial signature. The study may thus offer to develop a framework for exploiting this microbial signature for early diagnosis and prognosis of PCa development.